The perpetuation of stratification in market environments - markets and corporate power, institutions, and complex systems dynamics - Schwardt Henning (Panoeconomicus)
We consider how market environments can perpetuate the stratification of societies and economies. Markets are sets of institutions. These institutions are emergent outcomes of interactions in ongoing socio-economic processes. They entail societies’ rules, norms and values; and market environments and agents’ behavior therein will reflect them. Markets are also complex systems. Complex systems dynamics allow us to identify additional endogenous mechanisms contributing to the perpetuation of stratified structures in market economies. In capitalism’s drive towards concentration and centralization, and the concomitant consolidation of corporate power, further factors leading to stratified socio-economic outcomes emerge. We formulate policy considerations based on the analytical results presented. One focus is what measures may help reduce stratification and change the dynamics that reconstitute it. The other focus draws on the fact that policies are an output of the system, which means that changes to the structure itself may have to be required to advance changes that can have an equitable impact.